Zero Dynamics Analysis for Inverse Decoupling Control of Asynchronous Traction Motor - xin Li; Haiying Dong; Enen Ren (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Considering the problem for inverse system method in EMU AC induction traction motor linear decoupling, the zero dynamics subsystem will be separated from the original dynamic system through coordinate transformation. Firstly, a getting method for zero dynamics of the multiple input multiple output nonlinear system is discussed when γ＜n. Second, the zero dynamics analysis for five order nonlinear model of asynchronous traction motor which base on the stationary coordinate system is given by using inverse decoupling method. The analysis results show that if the stability of the zero dynamics can be ensured, then the entire linearization of original nonlinear system is not necessary, need only partial linearization which effect on the external dynamic portion. The inverse decoupling process of asynchronous traction motor can be simplified by this conclusion.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3354